Digital Marketing Berbasis Kearifan Lokal: Membangun Identitas Produk UMKM NTB Dalam Pasar Global: Digital Marketing; Global Market; Local Wisdom; MSME; Product Identitiy - Adi Prayuda, I Putu Septian; Basit, Abdul; Sakti, Reza Arviciena; Zahari , Yudhi Kurniawan (Universitas Pamulang, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in West Nusa Tenggara (NTB) have great potential thanks to their unique cultural richness, yet they face major challenges in global market competition due to limited digital literacy and suboptimal promotional efforts. This study aims to understand how the application of digital marketing based on local wisdom can strengthen the product identity of NTB’s MSMEs and increase their competitiveness in the international market. Using a qualitative method through literature studies and in-depth interviews with MSME actors, digital marketing practitioners, and cultural figures, this research found that integrating cultural elements such as traditional motifs, product origin stories, and authenticity narratives into digital content can create unique product identities and build emotional connections with consumers. This strategy has proven effective in increasing social media engagement, adding value to products, and supporting the preservation of local culture. However, the main challenges still lie in low digital literacy, limited resources, and inconsistency in conveying cultural narratives. Therefore, this study recommends strengthening culturally based digital marketing training, multi-stakeholder collaboration, and authentic content strategies aligned with NTB’s cultural values as key factors for MSMEs to compete successfully in the era of globalization.